Model for Strengthening Citizen Journalism through Local Communities in Government - Rafid, Rahmad; Supriadi, Supriadi; Tefa, Angelina Jesica (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2025)
This study develops a model for strengthening citizen journalism through local communities as a form of public participation in transparent and accountable governance. The research addresses the increasing public role in disseminating information amid rapid technological growth, which often lacks structured support and leads to misinformation. Using a qualitative descriptive case study approach, data were collected through semi-structured interviews, participatory observations, and documentation, then analyzed thematically with triangulation for validity. The findings indicate that strengthening citizen journalism through local communities relies on three main pillars: (1) an inclusive and coordinated community organization, (2) an integrated two-way communication system between citizens and government (G2C), and (3) local government support through media literacy training, verification mechanisms, and legal protection. Case studies of Radio KDS 8 and Community Information Groups (KIM) in Malang demonstrate that empowered local communities effectively channel public aspirations, verify information, and serve as communicative bridges between citizens and government. The proposed model offers a strategic policy framework to promote participatory governance, enhance digital democracy resilience, and build public trust. Theoretically and practically, it contributes to improving information accountability, reducing misinformation, and strengthening citizen engagement in local governance.